2015
DOI: 10.1080/ac.70.2.3073508
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus: the influence of disease-related and classical risk factors on intima media thickness and prevalence of atherosclerotic plaques - a preliminary report. Beneficial effect of immunosuppressive treatment on carotid intima media thickness

Abstract: We found a correlation between atherosclerosis and several classical cardiovascular risk factors and disease-related factors. A beneficial effect of continuous immunosuppressive treatment on IMT suggests that appropriate disease control with steroid-sparing agents may protect against atherosclerosis in SLE patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 0 publications
3
2
0
Order By: Relevance
“… 5 Previous studies have demonstrated that immunosuppressive treatment reduced endothelial damage and improved patient condition in atherosclerosis. 34 , 35 This finding agrees with our result showing that the PAOD risk was higher in SLE patients without immunosuppressive treatment than in SLE patients with various treatments. Thus, we hypothesized that suppression of inflammation and disease control might reduce cardiovascular risk in patients with SLE.…”
Section: Discussionsupporting
confidence: 92%
“… 5 Previous studies have demonstrated that immunosuppressive treatment reduced endothelial damage and improved patient condition in atherosclerosis. 34 , 35 This finding agrees with our result showing that the PAOD risk was higher in SLE patients without immunosuppressive treatment than in SLE patients with various treatments. Thus, we hypothesized that suppression of inflammation and disease control might reduce cardiovascular risk in patients with SLE.…”
Section: Discussionsupporting
confidence: 92%
“…18,19 Also, increased reactive oxygen radicals and apoptosis as well as endothelial dysfunction leads to an accelerated atherosclerotic process in patients with SLE. 20 A high cIMT was reported in patients with SLE 21,22 as in our study.…”
Section: Discussionsupporting
confidence: 71%
“…This agrees with Sazliyana who stated that there was no correlation between disease activity measured by SLEDAI and thickened cIMT, since atherosclerosis itself is the result of a chronic insult to the vessel wall, perhaps measuring disease activity at the current study time point is not a good indicator of the overall activity or severity of lupus activity throughout the course of the disease [26]. Our results disagree with Kisiel who stated that IMT was associated with SLEDAI [27]. This could be explained by different technical methods used and/or absence of standardization.…”
Section: Discussionsupporting
confidence: 67%